The Role of Parepare Port in Trading and Shipping of Rice Commodities in South Sulawesi, 1930−1942 - Syafaat Rahman Musyaqqat; Didik Pradjoko (Journal of Maritime Studies and National Integration, 2020)
The economic historiography in trading and shipping activity during the 20th century often linked up to the role of Makassar as the main port in Sulawesi supported the exchange of beneficial commodities, such as copra which was -deemed as the “green gold” of the archipelago. In terms of becoming the most prominent entrepot for international trading and shipping, there were also several ports in South Sulawesi that played a vital role in establishing a connection to the outside world with much more variety of commodities. It could find other commodities, such as rice, which was transported all across the archipelago. Thus, this article argues that the Port of Parepare had a significant role in the trading and shipping of rice commodities in South Sulawesi, during the age of colonial administration (1930-1942). Through the historical method, the findings show that the Port of Parepare, throughout the 1930s, the Port of Parepare was not just a collecting port for Makassar, but also became the supplier of rice from the coastal area to the hinterland. Such synergistic collaboration, between the economic potential of the hinterland, agricultural intensification program, and colonial government regulation, encouraged the Port of Parepare to become the most imminent rice exporter in South Sulawesi during the 1930s. Moreover, within the same period, Parepare was also establishing interisland networks